Conversion of Waste Cooking Oil into Biodiesel - Fareez Zulhaqeem Zahadi,; Syamir Syakirin Yahya,; Siti Noraiza Ab Razak, (Multidisciplinary Applied Research and Innovation, 2023)
Waste cooking oil (WCO) has become one of the major environmental pollutants due to its improper disposal, thus putting the ecosystem at risk. Therefore, this study aims to produce biodiesel through the transesterification process of WCO and elucidate its chemical and physical properties. Sodium hydroxide is the catalyst for this process, was dissolved in methyl alcohol before being mixed with WCO. The WCO and methyl alcohol mixture was left for a day and was then filtered and washed to obtain pure biodiesel. Results shows that the biodiesel produced from WCO has almost identical properties with biodiesel produced from other sources in terms of density and kinematic viscosity which are 0.85 kg/m3 and 5.76 mm2/s respectively. Fourier Transform Infrared spectroscopy spectrum analysis of biodiesel from WCO also shows similar functional groups being present in other biodiesels which contains C-O, C=O and C-H at 1168 cm-1, 1741 cm-1, and 2922 cm-1 respectively. Therefore, WCO can be used as an alternative source to produce biodiesel. Glycerin, the byproduct of biodiesel production is proposed to be further researched for its potential in producing other products in the pharmaceutical and cosmetics industry as well as soap production.